Bis(phosphine) Pd(II) and Pt(II) ethylene glycol carboxylates: Synthesis, nanoparticle formation, catalysis. (1st February 2023) - Scharf, Sebastian; Notz, Sebastian; Jeschke, Janine; Preuß, Andrea; Rüffer, Tobias; Wiese, Alexander; Künzel-Tenner, Andy; Schulze, Steffen; Hietschold, Michael; Lang, Heinrich
Graphical abstract: The synthesis, thermal behavior and solid-state structure of [M(O2 CCH2 (OCH2 CH2 )n OMe)2 (PR3 )2 ] (M = Pd, Pt; n = 0, 1, 2) is discussed. Their use for Pd and Pt NP formation and their application in heterogeneous catalysis is reported. Highlights: Synthesis and thermal decomposition of Pd/Pt ethylene glycol carboxylates. Thermal-induced metal nanoparticle formation by the single-source approach. Use of Pd NPs in Suzuki-Miyaura C, C coupling and Pt NPs in hydrosilylation. Abstract: The synthesis of [M(O2 CCH2 (OCH2 CH2 )n OMe)2 (PR3 )2 ] (M = Pd: R = Ph, 4a, n = 0; 4b, n = 1; 4c, n = 2. R = Bu, 4d, n = 0; 4e, n = 1; 4f, n = 2. M = Pt: R = Ph, 5a, n = 0; 5b, n = 1; 5c, n = 2. R = Bu, 5d, n = 0; 5e, n = 1; 5f, n = 2) by the reaction of [MCl2 (PR3 )2 ] (M = Pd: 1a, R = Ph; 1b, R = Bu. M = Pt: 2a, R = Ph; 2b, R = Bu) with [AgO2 CCH2 (OCH2 CH2 )n OMe)] (3a, n = 0; 3b, n = 1; 3c, n = 2) in the ratio of 1:2 is discussed. The structure of 4b, c, 5d and [Pd(Cl)(O2 CCH2 OMe)(PPh3 )2 ] (6 ) in the solid state, as determined by single crystal X-ray structure analysis, displays a tran s (4b, c, 6 ) or cis (5d ) configuration of the ligands with syn -oriented ethylene glycol carboxylates at M. TG-MS (TG = thermogravimetry, MS = mass-spectrometry) studies verified that the respective complexes decarboxylate between 140 and 270 °C to give [M(CH2 (OCH2 CH2 )n OMe)2 (PR3 )2 ], after which PR3 is released followed by reductive elimination of the ethylene glycol functionalities (and further decomposition to lower boiling C, H, O species) upon M formation. Thermal decomposition of neat 4a -f and 5a -f (TG, TG-MS (4c, 4f )) produced M(0), while in solution (4f ) narrow-sized Pd nanoparticles (=NPs) of size 2(±1)–4(±1) nm were formed as confirmed by TEM and XRD studies. Complex 5f produced uniform Pt NPs of a broader size distribution (2(±1)–8(±1) nm). The use of the Pt NPs in the hydrosilylation of PhCCH with HSiR3 (R = Et, Ph) displayed minor catalytic activity, while the Pd NP possesses good performance in the Suzuki-Miyaura C, C cross-coupling of phenylboronic acid and different aryl bromides, as characteristic for NP-assisted catalysts.